A och O om akademiska ord - Om framtagning av en svensk akademisk ordlista - Sköldberg, Emma; Kokkina, Sofie Johansson (Nordiske Studier i Leksikografi, 2012)
This paper reports on the development of a new electronic Swedish academic word list, which will be based on a corpus consisting of texts from a wide range of university subject areas. (Cf. the English Academic Word List, AWL, presented in Coxhead 1998, 2002.) Once finalized, the dictionary and corpus will be publicly available. The aim of the word list is to provide an indication of important words for university students, in particular non-native speakers of Swedish. In order to succeed in higher education, the mastery of an academic vocabulary may be crucial. A closely related study of extraction of a school-related vocabulary of secondary school textbooks is the OrdiL project (Lindberg & Johansson Kokkinakis 2008). The Swedish academic word list will be developed in cooperation with other Nordic countries in a multi-disciplinary project focusing on language use in Nordic academic settings.